Analysis of slope stability on tropical residual soil - M. F., Zolkepli; Mohd Fakhrurrazi, Ishak; M. S.I., Zaini (IAEME Publication, 2018)
Tropical residual soil is a product of chemical weathering, thus its characteristics are dependent upon environmental factors such as parent rocks, climate, topography and age. This type of soil can be found in many countries all over the world, especially in the tropical region. Since there are many accident happens due to slope failure, a comprehensive laboratory study need to be conducted in order to determine the properties of soil located at Pahang Matriculation College. Several experiments involving physical index and engineering properties of soil are conducted. The typical tropical residual properties are showed and can be considered as sandy SILT of high plasticity as suggested by previous researchers. The result from CIU testing give 9 kPa of cohesion and 25⁰ of friction angle while unsaturated friction angle was assumed 21⁰. From the slope analysis at Pahang Matriculation College, for a saturated slope (0 kPa suction), the FOS value using Fellenius’s method is 1.199 while Bishop’s method give 1.262 which the difference is 5.25 %. For an unsaturated slope (20 kPa suction), the FOS using using Fellenius’s method is 1.492 while Bishop’s method give 1.550 which the difference is 3.89 %. The results concluded that FOS value of slope is always higher if calculated using Bishop’s method compare to Fellenius’s method.